2012
DOI: 10.1111/tbed.12018
|View full text |Cite
|
Sign up to set email alerts
|

Bovine Brucellosis in Argentina and Bordering Countries: Update

Abstract: Bovine brucellosis is a zoonotic disease spread worldwide. The infection in cattle is predominantly caused by Brucella abortus and is usually detected in pregnant females through abortions. The disease is endemic in Argentina; however, infection in humans is underestimated and often not reported. The prevalence of bovine brucellosis in countries bordering Argentina is quite variable: 0.04% in Uruguay, 10.20% in the north and 0.06% in the south of Brazil, 0.2% in Chile, 3.15% in Paraguay and 2.27% in Bolivia. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 7 publications
0
26
0
1
Order By: Relevance
“…Despite their availability, conventional brucellosis vaccines are only approximately 70% efficacious [24, 25]. Although the smooth vaccine, B. abortus S19, has been replaced with the rough RB51 vaccine in the US [26], S19 is still used in many countries including India [27] and Argentina [28]. S19 tends to be more pathogenic and can cause abortion in 3.2% of pregnant cows following subcutaneous vaccination [29] or 100% following i.v.…”
Section: Discussionmentioning
confidence: 99%
“…Despite their availability, conventional brucellosis vaccines are only approximately 70% efficacious [24, 25]. Although the smooth vaccine, B. abortus S19, has been replaced with the rough RB51 vaccine in the US [26], S19 is still used in many countries including India [27] and Argentina [28]. S19 tends to be more pathogenic and can cause abortion in 3.2% of pregnant cows following subcutaneous vaccination [29] or 100% following i.v.…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiological surveillance is important because the commercialization of unpasteurized dairy products can pose a threat to human public health. In addition, zoonotic infections, such as brucellosis and TB, are common, insidious, and persistent problems for livestock farmers in general in developing countries (Aznar et al 2014; Roess et al 2015). Despite control measures and sanitation efforts, zoonotic disease outbreaks have been reported in Colombia (Morales and Combariza 2004; González et al 2007; Tique et al 2009, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Other countries, such as Canada and the United States, still have some cases, which are directly connected to infections in wild animals (RAGAN, 2002;OIE, 2014). In various South American countries, sero-epidemiologic studies have demonstrated a large variation in the apparent prevalence of cattle seropositive for B. abortus, albeit differences in geographical stratification and methodologies; from 2.10% in Argentina (AZNAR et al, 2014(AZNAR et al, ), 3.15% (2000 to 1.62% (the first six months of 2014) in Paraguay (BAUMGARTEN, 2002;SENACSA, 2014), 1.22% in Bolivia (MANRIQUE et al, 2005), 0.2% in Chile (LOPETEGUI, 2011), and 0.04% in Uruguay (GARIN, 2011).…”
Section: Introductionmentioning
confidence: 99%